Vasyl Kovalchuk, Artem Androsenko, Anna Boiko, Vasyl Tomash, Oleksandr Derevyanchuk. Development of Pedagogical Skills of Future Teachers of Labor Education and Technology by means of Digital Technologies // IJCSNS International Journal of Computer Science and Network Security. – 2022. – V. 22, №9, P. 551-560. - Kovalchuk, Vasyl; Androsenko, Artem; Boiko, Anna; Tomash, Vasyl; Derevyanchuk, Oleksandr (My University, 2022)
The influence of digital technologies on the effectiveness of the development of pedagogical skills of future teachers of labor education and technology has been studied. The essence of the concept of "pedagogical skills of future teachers of labor education and technology" has been clarified. It is interpreted as a higher level of development of the professional characteristics of the individual, which is determined by psychological and pedagogical preparation, the ability to optimally solve pedagogical tasks, innovation, creativity, mobility, a high level of development of pedagogical techniques and pedagogical thinking, professional and pedagogical competence, etc. Digital tools that contribute to the development of pedagogical skills are singled out, namely: Learningapps, Educaplay, Padlet, Flippity (for the development of critical thinking, generalization of the learned material, its verification and consolidation); MindMeister, Cacoo, Bubblus, Mindomo (contribute to the development of group work organization skills, reflection); Glogster, ThingLink (for organizing independent work and self -development), Toki-Toki, Powton, Kahoot, Plickers, PearDeck (tools that promote the development of creative abilities). Attention is focused on the importance of introducing STEM technologies in the process of training future teachers of labor education and technologies; those technologies that contribute to the development of pedagogical skills are highlighted. The results of the conducted experimental research are described. The study included: a survey of teachers of labor training and technologies, a survey of teachers and Masters of the specialty 014 Secondary education (Labor training and technologies) of full-time and part-time forms of education of the Glukhiv National Pedagogical University named after O. Dovzhenko. According to the results of the research, the most effective tools for developing the pedagogical skills of future teachers of labor training and technology, as well as the key problems faced by educators in the process of introducing digital technologies into the educational process are identified: lack of clear instructions on the use of digital technologies; low level of readiness to use digital technologies in professional activities; low ability to share experience with colleagues. The main obstacles pointed out by the respondents are: limited access to the Internet; lack of experience with digital technologies; lack of information about digital technologies; unclear instructions from the administration of general secondary education institutions; lack of motivation.
Keywords: digital technologies pedagogical skill future teachers of laboreducation and technology professional training educationalprocess